Implications of Counselling, Psychological and Social Services on Academic Performance of Primary School Pupils in Southwest, Nigeria - Oluwayemisi, Alebiosu, Eunice; Akin, Akintoke, Victor; Israel, Oginni, Omoniyi (Contemporary Research in Education and English Language Teaching, 2021)
The study examined implications of counselling, psychological and social services on academic performance of primary school pupils in Southwest, Nigeria. The study adopted a descriptive survey research design. The population consisted of all primary school teachers in Southwest out of which 1006 teachers were selected from the three sampled states in Southwest, Nigeria. Multistage sampling procedure was used to select sample for the study. The instrument used for data collection was tagged Implications of Counselling, Psychological and Social Services Questionnaire “(CPSSQ)” and a proforma titled “Data Retrieval Format” (DRF). CPSSQ comprised of two sections. Section A sought information on the bio data of the respondents while Section B was used to elicit information on implications of psychological, emotional and social dimensions of the pupils’ health. The instrument was validated by experts in Guidance and Counselling, Human Kinetics and Health Education and Tests and Measurement. The reliability of the instrument was ensured by using Pearson’s Product Moment Correlation analysis and had reliability co-efficient of 0.86, which was adjudge high enough and considered the instrument to be reliable. One general question was raised and one null hypothesis was formulated for the study. The study revealed that counselling, psychological and social services had implications on school health programme. It was therefore recommended that the status of school health programme in Southwest should be improved upon, considering its importance to the survival and academic performance of the school pupils.